Effect of Parental Modelling, Parental Control, and Information Exposure on Food Selection - Hilda Fauziah; Lilik Noor Yuliati (Journal of Consumer Sciences, 2017)
Food selection is the way a person considers choosing foods to eat for some reasons – mood, simplicity, sensory appeal, a natural ingredient in food, price, weight control, familiarity, and ethical issues. This study aimed to analyze the influence of parental modeling, parental controls, and information exposure on food selection on college student. The scope in food selection in this study is limited to vegetables. The method in this study used a survey on adolescent perceptions towards the parents socialization in the past. Data were collected by self-administered, in which questionnaires were filled by the respondents of 288 IPB PPKU students selected with cluster random sampling. Data were analyzed using descriptive analysis, different test and multiple linear regression. Regression analysis showed that 30.5 percent of parental modeling variable in indirect modeling dimension and parental controls affected the food selection. Other variables, such as gender and age of the student's mother also influenced the food selection.